Endovascular Repair of Traumatic Isthmic Ruptures: Special Concerns - Patelis, Nikolaos; Katsargyris, Athanasios; Klonaris, Chris (Frontiers in Surgery, 2017)
Injury of the aortic isthmus is the second most frequent cause of death in cases of blunt traumatic injury. Conventional open repair is related to significant morbidity and mortality. Thoracic endovascular aortic repair (TEVAR) has increasing role in traumatic isthmic rupture, as it avoids the thoracotomy-related morbidity, aortic cross clamping, and cardiopulmonary bypass. Additionally to the technical difficulties of open repair, multi-trauma patients may not tolerate the manipulations necessary to undergo open surgery, due to concomitant injuries. TEVAR is a procedure easier to perform compared to open surgery, despite that a considerable degree of expertise is necessary. Direct comparison of the two methods is difficult, but TEVAR appears to offer better results than open repair in terms of mortality, incidence of spinal cord ischemia, renal insufficiency, and graft infection. TEVAR is related to a—statistically not significant—trend for higher re-intervention rates during the follow-up period. Current guidelines support TEVAR as a first-line repair method for traumatic isthmic rupture. Certain specific considerations related to TEVAR, such as the timing of the procedure, the type and oversizing of the endograft, heparinization during the procedure, the necessity of cerebrospinal fluid drainage, type of anesthesia, and the necessary follow-up strategy remain to be clarified. TEVAR should be considered advantageous compared to open surgery, but future developments in endovascular materials, along with accumulating long-term clinical data, will eventually improve TEVAR results in traumatic aortic isthmic rupture (TAIR) cases. This publication reviews the role, outcomes, and relevant issues linked to TEVAR in the repair of TAIR.